Utilisation de l'eau tritiee dans la recherche sur l'elevage en Afrique: Theorie, application, methodologie et lacunes potentielles de la technique - Nicholson, M.J. (1987)
Presents a theoritical outline of the techniques in the use of tritiated water (HTO) which can be used to estimate total body water, body composition, water turnover, milk intake and feed intake. Highlights its potential errors and gives a comprehensive methodology for the use of tritiated water under field conditions.